Powering and grounding of electronic equipment (Power quality)
This program continues the discussion of system and facility grounding by focusing on the powering and grounding of electronic equipment. It identifies various types of electronic equipment and discuss unique features that distinguish this equipment from other types of customer load. It also covers recommended methods for powering sensitive equipment. This includes circuits, equipment, wiring, and the application of power conditioning equipment for lightning and surge protection. It also examines the various grounding considerations for sensitive equipment, including insulated equipment grounds and high frequency referencing systems. Applicable industry standards for powering and grounding of sensitive equipment are also referenced.